Intriguing Heteroleptic ZnII bis(dipyrrinato) Emitters in the Far-Red Region With Large Pseudo-Stokes Shift for Bioimaging - Tabone, Roberta; Feser, Dominik; Lemma, Enrico D.; Schepers, Ute; Bizzarri, Claudia (Frontiers in Chemistry, 2021)
Novel heteroleptic Zn(II) bis(dipyrrinato) complexes were prepared as intriguing emitters. With our tailor-made design, we achieved far-red emissive complexes with a photoluminescence quantum yield up to 45 % in dimethylsulfoxide and 70% in toluene. This means that heteroleptic Zn bis(dipyrrinato) complexes retain very intense emission also in polar solvents, in contrast to their homoleptic counterparts, which we prepared for comparing the photophysical properties. It is evident from the absorption and excitation spectra that heteroleptic complexes present the characteristic features of both ligands: the plain dipyrrin (Lp) and the p-extended dipyrrin. On the contrary, the emission comes exclusively from the p-extended dipyrrin, suggesting an interligand nonradiative transition that causes a large pseudo-Stokes shift (up to 4600 cm-1). The large pseudo-Stokes shifts and the emissive spectral region of these novel heteroleptic Zn(II) bis(dipyrrinato) complexes are of great interest for bioimaging applications. Thus, their high biocompatibiliy with four different cell lines make them appealing as new fluorophores for cell imaging.